Psychological distress, burnout level and job satisfaction in emergency medicine: A cross‐sectional study of physicians in China. (15th October 2014) - Xiao, Yunbei; Wang, Jinguo; Chen, Si; Wu, Zhigang; Cai, Jian; Weng, Zhiliang; Li, Chengdi; Zhang, Xiaowei
Abstract Background Chinese physicians are not only facing heavy work overloads, but also abuse and injury because of patient mistrust of physicians. The primary objective of the present study was to measure psychological distress, burnout levels and job satisfaction among Chinese emergency physicians. Methods All the physicians from the EDs of three large general hospitals were recruited to undertake a questionnaire‐based survey from March to April 2012. The Hospital Anxiety and Depression Scale (HADS), Maslach Burnout Inventory‐General Survey and Minnesota Satisfaction Questionnaire were used. Correlations between job satisfaction and psychological distress and burnout were calculated using the Pearson correlation. An outcome was considered statistically significant if P < 0.05. Results Completed questionnaires were received from 205 (82.0%) physicians. The mean HADS anxiety subscale scores for the ED physicians and general population were 7.8 ± 3.4 and 4.7 ± 3.5, respectively (t = 1.526, P < 0.05). Additionally, the mean HADS depression subscale scores were 7.9 ± 3.6 and 4.7 ± 3.9, respectively (t = 1.567, P < 0.05). Fifty‐two (25.4%) exhibited high levels of career burnout. All aspects of job satisfaction were significantly lower in the ED physicians compared with a previous report (P < 0.05). Burnout was significantly negatively correlated with intrinsic and extrinsic job satisfaction in the sampled population. Conclusion Psychological distress is prevalent in this group of ED physicians, and it deserves attention from the whole society. Burnout and job satisfaction among ED physicians are at a 'moderate' level. Burnout is negatively associated with higher job satisfaction.